2019
DOI: 10.3390/brainsci9040087
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Effects of Acute Exercise on Episodic Memory Function: Systematic Review with Meta-Analysis

Abstract: Background: Accumulating research demonstrates that the timing of exercise plays an important role in influencing episodic memory. However, we have a limited understanding as to the factors that moderate this temporal effect. Thus, the purpose of this systematic review with meta-analysis was to evaluate the effects of study characteristics (e.g., exercise modality, intensity and duration of acute exercise) and participant attributes (e.g., age, sex) across each of the temporal periods of acute exercise on epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
138
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(152 citation statements)
references
References 86 publications
(104 reference statements)
9
138
4
1
Order By: Relevance
“…Previous studies have shown that acute exercise may, ptentially, improve retrospective memory. We, 28,29 along with others, 30,31 have summarized this effect elsewhere.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have shown that acute exercise may, ptentially, improve retrospective memory. We, 28,29 along with others, 30,31 have summarized this effect elsewhere.…”
Section: Discussionmentioning
confidence: 87%
“…The purpose of this experiment was not to evaluate the effects of acute exercise vs. no exercise on long-term memory function. This has already been evaluated and demonstrated in numerous experiments [1,2,10,11,17,20,[25][26][27][28]. Before any definitive conclusion that acute exercise prior to memory encoding and during early consolidation does not have a superior effect when compared to acute exercise only prior to memory encoding, future work is needed.…”
Section: Discussionmentioning
confidence: 97%
“…First, it may be worth considering a higher intensity bout of exercise, particularly during the early consolidation period, as emerging work suggests that higher intensity acute exercise may enhance episodic memory to a greater extent than moderate-intensity acute exercise [13]. Second, recent meta-analytic research demonstrates a greater effect size for long-term memory when the acute bout of exercise occurs later (vs. earlier) in the consolidation period [17]. As such, future work that evaluates this additive paradigm should consider positioning the acute bout of exercise approximately 4-h after memory encoding [17], as opposed to immediately after memory encoding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations